Complications of the surgical treatment of esophageal cancer and microbiological analysis of the respiratory tract - Vrba, Radek; Neoral, Cestmir; Vomackova, Katherine; Vrana, David; Melichar, Bohuslav; Lubuska, Lucie; Loveckova, Yvona; Aujesky, Rene (Biomedical papers, 2020)
Aim: The aim of this study was to reduce the severe respiratory complications of esophageal cancer surgery often leading to death. Methods: Two groups of patients operated on for esophageal cancer were evaluated in this retrospective analysis. The first group was operated between 2006-2011, prior to the implementation of preoperative microbiological examination while the second group had surgery between 2012-2017 after implementation of this examination. Results: In total, 260 patients, 220 males and 40 females underwent esophagectomy. Between 2006-2011, 113 (87.6%) males and 16 (12.4%) females and between 2012-2017, esophagectomy was performed in 107 (81.7%) males and 24 (18.3%) females. In the first cohort, 10 patients died due to respiratory complications. The 30-day mortality was 6.9% and 90-day was 9.3%. In the second cohort, 4 patients died from respiratory complications. The 30-day mortality was 1.5% and 90-day mortality was 3.1%. With regard to the incidence of respiratory complications (P=0.014), these occurred more frequently in patients with sputum collection, however, severe respiratory complications were more often observed in patients without sputum collection. Significantly fewer patients died (P=0.036) in the group with sputum collection. The incidence of respiratory complications was very significantly higher in the patients who died (P<0.0001). Conclusion: The incidence of severe respiratory complications (causing death) may be reduced by identifying clinically silent respiratory tract infections.
Keywords: esophageal cancer; respiratory complications; mortality; morbidity; preoperative examination